2017
DOI: 10.1177/0022042617704004
|View full text |Cite
|
Sign up to set email alerts
|

“Just Doing a Favor for a Friend”: The Social Supply of Ecstasy Through Friendship Networks

Abstract: The current project focused on the “not for profit” supply of illicit drugs within social networks. The aims of the study were to (a) explore the characteristics of social supply of ecstasy and the typical ways in which social dealing occurs, and (b) explore the benefits of social supply as perceived by those who engage in social supply. Overall, the results suggest that social supply of ecstasy occurs in dense, closely knit friendship networks and that mutual supply may be common. Users within friendship netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…Indeed, mutual supply networks appear to be common among NPS consumers, with many individuals both sourcing from and supplying to friends. This is consistent with previous research showing that individuals within friendship groups source drugs from, and concurrently supply to, group members to ensure a consistent supply of quality product and to minimise risks of health harms and criminal justice consequences (Bright & Sutherland, Under Review; Lenton et al, ; Nicholas, ).…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, mutual supply networks appear to be common among NPS consumers, with many individuals both sourcing from and supplying to friends. This is consistent with previous research showing that individuals within friendship groups source drugs from, and concurrently supply to, group members to ensure a consistent supply of quality product and to minimise risks of health harms and criminal justice consequences (Bright & Sutherland, Under Review; Lenton et al, ; Nicholas, ).…”
Section: Discussionsupporting
confidence: 90%
“…The findings suggested these methods were appealing primarily because of convenience and the absence of any financial cost. These results correspond with research suggesting that forms of social supply can be cost-effective and convenient methods of accessing illicit drugs (Bright & Sutherland 2017;Coomber, Moyle & South 2015;Potter 2009). The restricted availability and variable pricing of illicit pharmaceutical opioids relative to other illicit drugs may contribute to the desire to use social supply activities to acquire these drugs.…”
Section: Discussionsupporting
confidence: 87%
“…Police detainees have also reported that they commonly buy or get methamphetamine for free from relatives and friends, and that many use 'closed' markets, such as a friend's home, rather than public 'open' markets (Doherty forthcoming). Other research has suggested that social supply is also important in the markets for cannabis (Belackova & Vaccaro 2013;Lenton et al 2015;Nicholas 2008) and ecstasy (Bright & Sutherland 2017;Nicholas 2008). Friendship groups appear to play a smaller role in the distribution of heroin, which is more commonly sold by dealers in open markets (Mouzos et al 2007;Nicholas 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Gifting is part of drug transfer, too (Jacques & Wright, 2008a). A significant percentage of users and dealers act altruistically (Bright & Sutherland, 2017; Harrison, Erickson, Korf, Brochu, & Benschop, 2007). Perhaps more than any other drug, marijuana is known as a beacon of generosity (Zimmerman & Wieder, 1977).…”
Section: Illustrations Of the Drug-involved Pain/pleasure Frameworkmentioning
confidence: 99%